Performance of early weaned calves fed lasalocid - Anderson, K.L.; Nagaraja, Tiruvoor G.; Morrill, J.L.; Reddy, P.G.; Avery, T.B.; Anderson, N.V. (Kansas Agricultural Experiment Station, 2012)
Twenty-two newborn, bull calves were used to determine the effects of lasalocid on growth and feed intake of early-weaned calves from week 1 to 12. Calves were assigned to lasalocid or control groups on day 3. Lasalocid-fed group received lasalocid in milk from day 4 to 7 and in milk and pre-starter from days 7 to 14 and in starter feed from weeks 2 to 12. Lasalocid-fed calves had a significantly higher feed consumption and greater weight gain than calves that did not receive lasalocid. The difference became apparent only after 6 wk of age. Lasalocid appears to be a beneficial feed additive for newborn calves.
Keywords: Dairy; Performance; Lasalocid; Feed consumption; Weight gain